QCGN to Air Canada : Apology Alone Cannot Undo Damage to English-speaking Quebec - Quebec Community Groups Network (QCGN) (2021)

QCGN Eager to Collaborate with New Official Languages Minister Ginette Petitpas Taylor - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Congratulates Parties for Federal Election - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Urges English-speaking Quebecers to Vote for Best Local Candidate - Quebec Community Groups Network (QCGN) (2021)

Townshippers' Association Reacts to Bill C-32 - Townshippers' Association (2021)

QCGN Statement on Government of Canada’s Proposed Changes to the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

QCGN Statement on Murder of Muslim Family in London, Ontario : Human Rights and Freedoms Are Not to be Taken for Granted - Quebec Community Groups Network (QCGN) (2021)

QCGN Supports Commissioner's Call for Symmetry in the Official Languages Act - Quebec Community Groups Network (QCGN) (2021)

Many Reasons to Participate in Census - Quebec Community Groups Network (QCGN) (2021)
Keywords: Official Language Minority Community (OLMC)

The Official Languages Reform Project - Townshippers' Association (2021)
The February 19th, 2021 position paper put forth by the Canadian Federal Government addressed important issues raised by organizations representative of Canada’ s English-speaking minority language community, including several of those championed by Townshippers’ Association in consultations on the modernization of the Official Language Act (OLA) in 2017, 2018, and 2019 While the Association supports changes designed to improve accountability in its implementation, increase the transparency of federal transfer payments to provinces, and provide increased support for Official Language Minority Communities (OLMC) institutions, it reminds the Canadian Government of its legal responsibility to protect, support and defend the rights of both of its OLMCs, wherever they may be located, and cautions against strengthening the OLA in ways that promote asymmetry between Canada’s Official Languages.
Keywords: Official Language Minority Community (OLMC)

What Exactly is the Notwithstanding Clause, and Why Does it Matter? - Quebec Community Groups Network (QCGN) (2021)

Quebec Community Groups Network Preliminary Analysis of Bill C-13 : An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2021)
This document presents an overview of Bill C-13. This is not a comprehensive analysis of the Bill. Rather, it is informed and directed at priority areas of the QCGN.

Understanding an Official Language Minority Community - Quebec Community Groups Network (QCGN) (2021)
Keywords: Official Language Minority Community (OLMC)

Federally Regulated Businesses and the New Languages Landscape - Quebec Community Groups Network (QCGN) (2021)

English and French : Towards the Substantive Equality of Official Languages in Canada - Quebec Community Groups Network (QCGN) (2021)
The Government of Canada’s paper on official language reform captures important demands made by the English-speaking community of Quebec during consultative processes related to the modernization of the Official Languages Act. There is reason for optimism around proposals for an expanded role of Treasury Board and power of the Commissioner of Official Languages in the implementation of the Act. And there are opportunities for increased support to our community’s institutions and provisions for more transparency on federal transfers directed towards our vitality; proposals that are tempered by the need for provincial cooperation.

By the Numbers : How are Communities Counted? - Quebec Community Groups Network (QCGN) (2021)

Canada Must Not Abandon its Leadership on Official Languages - Quebec Community Groups Network (QCGN) (2021)

Official Languages, Diversity, and Canada's Place in the World - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Learning English and French - Canada. Office of the Commissioner of Official Languages (2021)

What Canadians Think About Official Bilingualism and the Official Languages Act - Canada. Office of the Commissioner of Official Languages (2021)